Modulation Transfer Function Evaluation of Scintillation Camera and Rectilinear Scanner - Alvi, Zahoor M.; Bennett, Leslie R. (Nuklearmedizin - NuclearMedicine, 1970)
A simple film density approach was used to obtain modulation transfer functions for a scintillation camera. Counting rate was measured in the case of rectilinear scanner. Point sources were prepared of 131I and 99mTc and point source images were obtained on X-ray film.Density distribution along the diameter of the images was converted into corresponding exposure values. Line spread functions were obtained as areas under the distribution curves and then MTF was solved for each spatial frequency considered. Plots of MTF versus spatial frequency show in one glance the relative responses of either the two imaging systems or the responses of one imaging system for two different commonly used radionuclides.